Double Hydroboration of Quinolines via Borane Catalysis: Diastereoselective One Pot Synthesis of 3‐Hydroxytetrahydroquinolines. Issue 2 (30th September 2019) - Kim, Eunae; Jeon, Hyun Ji; Park, Sehoon; Chang, Sukbok
Abstract: Described herein is an organoborane‐catalysed consecutive borylative reduction of quinolines and isoquinolines to furnish tetrahydro(iso)quinolines bearing a C( sp 3 )−B bond β to the nitrogen atom. The installed C−B bond is oxidatively transformed to the hydroxy group in one pot. The present double hydroboration is proposed to proceed via a stepwise ionic mechanism involving a boronium ion. The stereo‐outcome was found to be dependent on the position (C2 vs C4) of the substituents in quinolines. Abstract :